Seasonal Conditions of Labor Demand: An Empirical Research on Employment Practices in Tourist Enterprises in Poland - Ewa KASPERSKA; Kamila RADLIŃSKA (Communications of International Proceedings, 2023)
Assuming that seasonal fluctuations are a component of short-term fluctuations and their course is similar to cyclical fluctuations within the business cycle, the article considers the adaptation of the theory of labor demand to the conditions of high seasonal variability. The main goal of the article is to better understand the mechanism of labor demand in enterprises operating in conditions of high seasonality. To achieve the main goal of the article, an empirical research was also planned that focused on identifying the employment practices used by tourist enterprises and the employment conditions of workers in the coastal region in Poland. The results of the empirical research – a survey of enterprises – allowed for the conclusion that enterprises apply two employment practices in conditions of high seasonality. One in relation to seasonal workers (static approach to labor demand), the other to year-round workers (dynamic approach to labor demand). Both employment practices differ in, among others, methods of recruitment and employment, training and dismissals. Remuneration, on the other hand, is an element that unites workers employment practices.
Keywords: labor demand; labor hoarding; seasonality; tourist enterprise